2021
DOI: 10.1037/pla0000128
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of child-centered play therapy for children exhibiting behavioral problems: A meta-analysis.

Abstract: The authors conducted a meta-analysis exploring the effectiveness of child-centered play therapy (CCPT) approaches with children referred for disruptive behaviors across 23 between group studies (N = 908). Separate meta-analytic procedures were conducted for studies that implemented wait-list/no treatment and alternative treatment comparisons to estimate the aggregated treatment effect of CCPT approaches. Results revealed medium Hedges's g effect sizes for externalizing and overall problem behaviors compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…One moderate quality meta-analysis (Parker et al, 2021a , b ) found that child-centered play therapy led to reductions in externalizing and overall problem behaviors with medium effects. There were also reductions in aggressive behaviors, with small effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One moderate quality meta-analysis (Parker et al, 2021a , b ) found that child-centered play therapy led to reductions in externalizing and overall problem behaviors with medium effects. There were also reductions in aggressive behaviors, with small effects.…”
Section: Resultsmentioning
confidence: 99%
“…Publication bias: not ascertained; Magnitude of effect similar across studies. Follow-up times in studies typically about 1 year – longer term follow up was rare Losel and Beelmann ( 2003 ) High Risk of bias: low due to RCTs; Precision: overall, small to moderate effect sizes observed; Consistent findings reported across studies; CBT Interventions directly related to outcome of interests; Publication bias: not ascertained; Magnitude of effect: Mostly medium; Dose response: N/A; Findings on confounder (age) increases GRADE Maughan et al, ( 2005 ) Moderate Risk of bias: Some risk of bias, including RCTs and non-RCT with variability in study quality; Precision: Overall moderate to large effect sizes observed, effect size varied by study quality; Interventions directly related to pop of interest; Publication bias: not ascertained; Mostly moderate magnitude of effect; Dose–response: N/A; Menting et al, ( 2013 ) Moderate Risk of bias: Low risk of bias due to mostly RCTs; Precision: Small effect sizes observed; Consistent findings reported across studies; IY Interventions directly related to outcome of interests; Publication bias: not ascertained; Magnitude of effect: Mostly weak; Dose response: N/A Mingebach et al, ( 2018 ) Moderate Risk of bias: overall risk of bias rated as satisfactory in the paper, consists of meta-analyses; Precision: Moderate effect sizes observed, with risk of bias analyses within paper suggesting robust results; Consistent findings reported across studies; Parenting-based interventions directly related to pop of interest; Publication bias: risk of bias analyses from funnel plots and fail-safe Ns suggest some but small publication bias; Magnitude of effect: Moderate; Dose–response: N/A Nogueira et al, ( 2022 ) Moderate Risk of bias: low risk of bias due to all RCTS, but some studies did not report randomization/blinding; Precision: small effect sizes (secondary outcomes) and moderate effect sizes (all GTP targeted outcomes); Interventions related to outcome; Publication bias: not ascertained; Magnitude of effect: mostly moderate; Dose response: N/A Nye ( 2019 ) High Risk of bias: low due to RCTs; Precision: Moderate effect sizes observed; Consistent findings reported across studies; Intervention directly related to outcome of interest; Publication bias: not ascertained due to small number of studies; Magnitude of effect: Medium; Dose response: N/A Parker et al, ( 2021a , 2021b ) …”
Section: Methodsmentioning
confidence: 99%
“…Ray et al (2015) conducted a meta-analysis specific to CCPT in elementary schools, analyzing 23 studies from 1970 to 2011 and finding significant small to medium effect sizes that are similar to or greater than those of other studies of psychological interventions in schools. Most recently, Parker et al (2021) conducted a meta-analysis specific to children referred for disruptive or externalizing behaviors, analyzing 23 CCPT studies from 1999 to 2018, finding medium effect sizes that are similar to the effect sizes evidenced in Battagliese et al's (2015) meta-analysis of CBT for externalizing disorders, though the latter was not a play therapy meta-analysis.…”
Section: Core Principles and Research Behind Ccpt And Cbt Applied To ...mentioning
confidence: 93%
“…Synthesis of multiple meta-analyses indicated CCPT is an effective intervention in clinical and school settings, for children coming from both dominant and minoritized cultures (Bratton et al, 2005; Y. Lin & Bratton, 2015; Parker et al, 2021; Ray et al, 2015). A growing number of empirical studies further support the efficacy of CCPT with children across ethnicities, gender, and ability levels (e.g., Garza & Bratton, 2005; Lin & Bratton, 2015; Ogawa, 2007; Schottelkorb et al, 2020; Taylor & Ray, 2021).…”
Section: Ccpt Materialsmentioning
confidence: 99%